EFFECTS OF SERVICE QUALITY AND PHYSICAL ENVIRONMENT ON PATIENT SATISFACTION OF DARUSYIFA MULIA KARANG TENGAH CLINIC IN LEBAK BULUS. - Anhari, Agus Sulaiman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to find out how service quality, patient satisfaction and physical environment affect patient satisfaction, and how service quality and physical environment affect patient satisfaction. and impact on patient satisfaction. These are validity test, correlation coefficient reliability test, coefficient of determination, t-test and f-test, multiple regression test, simple regression test, data normality test, multicollinearity test, autocorrelation test, heteroskedasticity test and in this study all patients participated. Darusyifa Mulia Clinic in Karang Tenga, Lebak Bulus received a total of 6,637 people with Slovin formula in 2019, and 98 people participated in the study. According to the results of the product moment correlation coefficient calculation analysis, the value of the correlation coefficient is based on 0.747, so the results of the partial test (t test) between service quality and patient satisfaction show that the table t number > t value ( 7.268> 1.985 ), so that Ho is skewed , Ha is accepted, product moment correlation coefficient and correlation coefficient is 0.747, the physical environment of patient satisfaction shows the value (8.836 > 1.984), so Ho is rejected, Ha is accepted, the reliability test results, then the questionnaire item rca ( 0.838) > rtable. (0.198) with α = 5%, the variance of the patient satisfaction element variable (Y) can be reliably determined. According to the results of the F-test, the value of F count > f in the table is (59.823 > 3.09), the effect of service quality and physical environment. Keywords.: service quality, physical environment and patient satisfaction